Isolation, Molecular Identification and in vitro Antibiotic Susceptibility Testing of Mycoplasma agalactiae From Goats in Two Provinces of Kurdistan Region-Iraq. - Sulaiman, Rizgar R. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Mycoplasma agalactiae is one of the causal agents of classical contagious agalactia (CA). It occurs in many parts of the world and most notably in the Mediterranean Basin. The aims of this study were isolation and molecular identification of Mycoplasma agalactiae for the first time in Kurdistan region from goats showing contagious agalactia and in vitro evaluation of the activities of different antimicrobial against Mycoplasma agalctiae. During the period of January 2011 to November 2012 a total of 126 milk samples were collected (68 from Slemani governorate and 58 from Arbil governorate) from goats that had clinical signs of CA. Mycoplasma agalactiae was recovered from 102(81%) milk samples out of (126) divided as; 58 (85.3%) out of 68 milk samples in Slemani governorate were positive for M. agalactiae while 44(75.9%) out of 58 milk samples were positive in Arbil governorate. All isolates were confirmed by amplification of 1624 bp uvrC gene by PCR assay. GenBank accession number of the nucleotide and amino acid sequences of Slemani and Arbil isolates were reported in this study is (KC 594646), (KC 594647) respectively. The isolates in current work from both governorates were showed 99% homology to each other and the topology of the phylogenetic tree indicated that both field isolates were clustered together and they were belonging to sub linage that contain most of PG2 strains. Danofloxacine and Azithromycine showed a great effectiveness against all isolates and may be considered as standard treatment for CA in this region.
Keywords: Contagious agalactia Mycoplasma agalactiae uvrC gene antibiotic susceptibility